Analisis Optimalisasi Metode Curing terhadap Perilaku Mortar Geopolimer Berbasis Fly ash - Nur Rahmawan, Fatih; Sutriono, Bantot; Trimurtiningrum, Retno (Universitas Iskandar Muda, 2026)
Geopolymer is an environmentally friendly concrete based on pozzolanic materials rich in silica and alumina. The compound reacts with an alkali activator thru a polymerization process, resulting in binding properties. Geopolymer concrete generally requires an activation temperature of around 60℃ to enhance compressive strength, making it less practical for large-scale applications. Therefore, this study examines the most optimal room temperature curing method for the compressive strength of fly ash-based geopolymer mortar. The research uses 12M and an activator ratio of : of 1:1. The test specimens in the shape of cubes were cured using three methods: water curing, moist curing, and wrap curing. The compressive strength test was conducted at 7 and 28 days of age. The results show that at 7 days of age, water curing produced the highest compressive strength of 22.24 MPa. However, at 28 days of age, wrap curing produced the highest compressive strength of 47.09 MPa. This shows that wrap curing is capable of maintaining internal moisture and preventing water loss due to evaporation, thereby making the geopolymerization process more stable and forming a denser structure. Thus, wrap curing becomes the most optimal curing method because geopolymer does not require water as the main reaction component.Geopolymer is an environmentally friendly concrete based on pozzolanic materials rich in silica and alumina. The compound reacts with an alkali activator thru a polymerization process, resulting in binding properties. Geopolymer concrete generally requires an activation temperature of around 60℃ to enhance compressive strength, making it less practical for large-scale applications. Therefore, this study examines the most optimal room temperature curing method for the compressive strength of fly ash-based geopolymer mortar. The research uses 12M and an activator ratio of : of 1:1. The test specimens in the shape of cubes were cured using three methods: water curing, moist curing, and wrap curing. The compressive strength test was conducted at 7 and 28 days of age. The results show that at 7 days of age, water curing produced the highest compressive strength of 22.24 MPa. However, at 28 days of age, wrap curing produced the highest compressive strength of 47.09 MPa. This shows that wrap curing is capable of maintaining internal moisture and preventing water loss due to evaporation, thereby making the geopolymerization process more stable and forming a denser structure. Thus, wrap curing becomes the most optimal curing method because geopolymer does not require water as the main reaction component.